Back Cover: Synthesis, π‐Face‐Selective Aggregation, and π‐Face Chiral Recognition of Configurationally Stable C3‐Symmetric Propeller‐Chiral Molecules with a π‐Core (Chem. Eur. J. 19/2014). Issue 19 (5th May 2014) - Saito, Nozomi; Terakawa, Ryo; Yamaguchi, Masahiko
<x xml:space="preserve">Abstract</x> Right and left hands are mirror images to each other, and each of them has two distinguishable faces. When two hands lay one upon another, there are several modes of stacking depending on the combination of right/left hands and the two faces. In the same manner, C3‐symmetric propeller‐shaped compounds possess two distinguishable propeller‐chiral π‐faces, which can form seven modes of dimeric aggregates. It was found that one of them predominated both in the solid state and in solution. π‐Face‐selective aggregation and π‐face chiral recognition of propeller‐chiral molecules are described in the Full Paper by M. Yamaguchi et al. on page 5601 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>